Factors of variability of grammatical system of the Ukrainian language of 17th century - Naienko, Halyna (Ukrainian linguistics, 2017)
The article examines species of variance in the graphic, phonetic-phonological and grammatical systems, which should be taken into account in the preparation of the historical grammar dictionary, grammar annotation of historical texts. The author defines the dynamic processes which make it dependent on the example of theoretical guide treatise by I. Galyatovskyi “Order or method of compiling a sermon” (second half of 17th century). The author points to the various graphical representations of phonemes, formation of new paradigms and interference processes. Phonetic variability correlated to loss of reduced phonemes and formation of a new phoneme /i/. Grammatical variation appears due to the influence Old Church Slavonic language or borrowing new terms from Latin. Coexistence grammatical forms old and new types of inflection manifested primarily in conjugation. She also gives an example of a variative paradigm of the noun. Information about the author:Halyna Naienko – Dr Hab, Associate Prof. of the Department of the Ukrainian Language and Applied Linguistics; Institute of Philology; Taras Shevchenko National University of Kyiv (Ukraine).E-mail: halynanaienko@gmail.com__________References• Darchuk N.P. (2013) Komp’juterne anotuvannja ukrajins’koho tekstu: rezul’taty i perspektyvy: monohrafija [Computer’s annotation of the Ukrainian text: results and perspectives]. Kyiv: Osvita Ukrajiny, 544 p. (in Ukrainian).• Didenko N.M. (2013). Variantnist’ dijeslivnoji paradyhmy u staroukrajins’kykh pam’jatkax peršoji polovyny 17 stolittja [Variability of verb paradigm in old Ukrainian manuscripts of first half of the 17 century] (PhD Thesis), Kyiv, 18 p. (in Ukrainian).• Zakharov V.P. (2015) Istoricheskije korpusa i korpusnyje diakhronicheskije issljedovanija [Historical corpora and corpora-based diachronic investigations] (e-prodact), from https: //textualheritage.org /content/view/639/276/lang,russian/.• Kravchuk A.УE. (2010) Funkcionuvannja prykmetnykovyx form rodovoho vidminka odnyny v movi staroukrajins’kyx pam’jatok [The functioning of genitive forms of adjectives in the language of Old Ukrainian manuscripts]. Comparative studies of Slavic languages and literatures, no 12. pp. 101-109 (in Ukrainian).• Kulchyczkyj I. (2016) Korpus tekstiv jak lingvotexnichne pidgruntja vyjavlennja zmin v ukrajinskij movi [Corpora as a lingua-technological basis for studying changes in the Ukrainian language]. 20-21 centuries: Genre-style and lingvistic metamorphosis in the Ukrainian language and literature. Olomouc, pp. 269-297 (in Ukrainian).• Tsaralunga I. (2012) Jаvyšče variantnosti v konteksti lingvistychnykh studij [The phenomenon of variety within the context of lingvistic studies]. Actual problems of philology and translation studies, no 5, pp. 205-216 (in Ukrainian).• Tsaralunga I. (2015) Slovozminna variantnist’ vlasnykh nazv (za materialamy ukrajins’kykh hramot 14ho stolittja) [Inflectional variability of proper names (based on the Ukrainian manuscripts of the 14th century)]. Opera in onomastica, no 18, pp. 733-745 (in Ukrainian).
Keywords: history of the Ukrainian language, grammar dictionary of the Ukrainian language of the 17th century, variance of grammatical system, Old Ukrainian literary language, Old Church Slavonic